Analisis Stakeholders dalam Pengelolaan Objek Wisata Gili Trawangan di Kabupaten Lombok Utara - Yustisi, Mira Janu (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
Gili Trawangan is an area of ​​tourism in North Lombok regency which is most visited by tourists and travelers, which are foreign tourists and domestic tourists. The high number of tourist visits is supported by the number of tourism businesses that already exist in Gili Trawangan which can be ascertained that many stakeholders are involved in it. Every stakeholder has a relationship between each other. That Relationship is a must because in the management of tourism needs support among stakeholders in order to create a better management of tourism. The stakeholders analysis to help see about the relationships that occur between stakeholders in the management of Gili Trawangan tourist attraction. The method used in this research is a qualitative method. Data obtained from primary data and secondary data. The result of the research shows that stakeholders involved in the management of Gili Trawangan tourism object are Department of Culture and Tourism of North Lombok Regency, Winner District Government, Gili Indah Village Government, Cooperative of Gili Trawangan (Hotel, Bungalow, Dive Shop, Restaurant) , Gili Ecotrust, Karang Taruna, Turtle Observer Foundation, Labor Group, and Janur Indah Cooperative.The relationship between stakeho lders in the management of Gili Trawangan tourist object has not been going well, it can be seen base on four aspects. 1). The Communication among departments that does not run well which resulting in conflict among the stakeholders. 2). The Cooperation is not carried out between the three sectors (government, private and public), but only in the form of activities that do not have the power of law and written rules. 3). The Coordination aspect that occurs only when the activity will be carried out or the execution of a policy from the local government of North Lombok Regency and only determined by experts only (government). 4). The Collaboration is only related to tourism events, activity and promotion, so this Collaboration also involves only two sectors, government and private.